Skrifgebruik en Skrifgesag in die postmodernistiese konteks - Johan Janse van Rensburg (In die Skriflig, 2021)
Scripture use and Scriptural authority in the postmodernist context. This article focused on the burning issue of the authority of Scripture and the way that it is currently used in the Christian and theological community. The research was necessitated by the gap between academic epistemology and the use of the Bible in religious activity. The research illustrated how a different understanding of the authority and interpretation of the Bible caused a clear division in church and society, particularly in the Reformed churches. The aim of the research was to illustrate the current abuse of the Bible in religious debate to legitimise pre-conceived convictions on theological and ethical issues. It was found that, even within the Reformed tradition, the opposing use of Scripture has caused diversity in the church community; thereby causing a serious break in the unity of the church. During the research process, it became clear that a radical new approach to Scriptural interpretation opposed the traditional Reformed understanding of the application of the Bible as per the three main confessions of the Reformed faith. What influenced such a radical new way of Scriptural authority? It was found that an analysis of philosophical systems, leading to the postmodern era, clearly prepared the way for an approach to search for the so-called true meaning of the text behind the text. This new approach was juxtaposed against the Reformed use of Scripture in the immanent text of the Bible and application thereof in the Reformed confession.